The Influence of Individual Morality and Internal Control on the Tendency of Academic Fraud in Unismuh Makassar Students (At Muhammadiyah University of Makassar) - Saipul Wahyu (Yayasan Amerta Insan Unggul, 2022)
This study aims to analyze the influence of individual morality and internal control on the tendency of fraud occurrence at Muhammadiyah University Makassar. Individual morality and internal control are crucial factors in maintaining organizational integrity and credibility. This research employs a quantitative analysis method by collecting data through questionnaires distributed to staff and employees at the university. The collected data is analyzed using regression techniques to measure the relationship between individual morality, internal control, and the tendency of fraud occurrence. The results of this study are expected to provide insights into how individual morality and internal control play a role in preventing potential fraud within the university environment. These findings have important implications for policy planning and fraud prevention strategies in university and similar organizational settings